Democracy in Question? Direct Democracy in the European Union. (10th May 2018) - Adam, Elisenda Casanas; Kagiaros, Dimitrios; Tierney, Stephen
Abstract : Challenges posed to European integration by exercises of direct democracy at the national or sub-state level – EU response to referendums on internal constitutional matters – Greek, Scottish and Catalan referendum processes – Resilience of state nationalism and the complex pluralisation of identities below the level of the state